Identification of a missense variant in SPDL1 associated with idiopathic pulmonary fibrosis - Ryan S. Dhindsa (Nature Portfolio, 2021)
Ryan Dhindsa et al. conducted an exome-wide association study to identify a rare variant in SPDL1 as a risk factor for idiopathic pulmonary fibrosis (IPF). Their findings implicate mitotic checkpoint signalling as a new mechanism underlying IPF.